Functional Foods may be Dysfunctional: A South Asian Perspective - Bharti Kalra; Leepica Kapoor; Suneet Verma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2023)
This communication describes a few functional seeds and spices, commonly consumed in South Asia, which may impair the absorption of drugs that are used in diabetes and medical management. The aim of this article is to highlight the possibility of these foods having a ‘dysfunctional’, rather than functional effect on health. Physicians should include questions about the use of these spices in their history taking. Keywords: Diabetes, drug interactions, food interactions, seeds, semaglutide, spices, thyroxine.